Community Perceptions Regarding Chikungunya Vector Proof Housing In Lahore, Pakistan for Sustainable Development - Taj, Serena; Rana, Saleem Muhammad; Hassan, Amber; Faridi, Tallat Anwar; John, Akash (Pakistan BioMedical Journal, 2022)
Sustainable Development Agenda is gaining importance, acknowledging its importance right adaptation of interventions for housing regarding vector-borne disease prevention as suggested by “Keeping the Vector Out” can make cities and human settlements vector-proof and sustainable.Objective: To assess community perceptions regarding chikungunya vector-proof housing for sustainable development. MethodS: Descriptive cross-sectional study included 400 households of Aziz Bhatti Town, Lahore. A semi-structured questionnaire administered by personal interview method to the available and willing adult member of the household by Researcher with the environmental inspector and lady sanitary patrol of Dengue and Polio survey teams of DDO office Aziz Bhatti Town Lahore, using simple random sampling technique after consent and ethical approval. The questionnaire was pre-tested (Pilot). Data analyzed using SPSS 20.0. Results: Among 400 households interviewed, the majority 69.7% were living in houses that were built >9 years ago, 86.8 % were concrete. Climatic change and global warming can increase disease carried by mosquito AedesAegypti believed by 90.2 % and their impact can be mitigated by improved housing reported by 91.5%. Regarding community perceptions about vector-proof housing, 74.6% believed that improved house design can prevent entry and breeding of mosquitoes therefore, 86.3% screened windows doors and eaves, 83.0% believed that they always checked cracks and crevices in the wall, floor and roof and cemented them. But 58.7% believed that they do not consider mosquito prevention housing interventions as one of the important factors when constructing their house as among barriers 73.5% could not afford modern building materials, 73.5% lack detailed knowledge and 13.8% thought screening as an obstruction to ventilation. Dengue, Chikungunya, and Zika disease are spread by Aedes mosquito species believed by 78% who (agreed and strongly agreed) still 81.8% urged for health education regarding chikungunya vector proof housing.Conclusion: Housing improvement can mitigate the impacts of climatic change and vector-borne disease. But health program planners need to identify and facilitate the removal of barriers for adoption of Vector proof housing.